DECENT WORK ACCORDING TO THE ILO: A DEMOCRATIC CONCEPTION? CRITICAL ANALYSIS AS CLAIMED BY THE SOCIAL CONTRACT THEORY - Silvio Beltramelli Neto; Isadora Rezende Bonamim; Julia de Carvalho Voltani (Revista Eletrônica do Curso de Direito da UFSM, 2019)
Based on Jean-Jacques Rousseau's Theory of Social Contract and Boaventura de Sousa Santos's perception of the current crisis of this Contract, the article discusses the democratic nature of the ILO's adoption of the Decent Work concept, the tripartism and the social dialogue applied at the international level, when the Decent Work was elected as the guideline for ILO actions, as well as at the state level, when the brazilian National Decent Work Agenda was elaborated. Finally, it can be concluded that the conceptions of Decent Work and the National Decent Work Agenda, despite not being undemocratic, can not be considered sufficiently democratic, due to the crisis of the Social Contract, which directly affects the pillars of representative democracy and the socially inclusive function of labor, with the consequent weakening of the representativeness of trade unions and the role of State as a normalizing agent of social inequalities. The methods used were the hypothetical-deductive approach and the historical and bibliographic process methods.